Oxidation and Mechanical Behavior of Cr-Coated Laser Beam Welds Made from E110 Zirconium Alloy; Coatings; Vol. 12, iss. 11 - Kashkarov E. B. Egor Borisovich; Gusev K. S. Kirill Sergeevich; Ashikhmin D. A. Denis Aleksandrovich; Abdulmenova A. V. Anastasiya Vladimirovna; Sidelev D. V. Dmitry Vladimirovich (2022, 2022)
Title screen